ASSOCIATION OF LIPID PROFILES WITH 10-YEAR ATHEROSCLEROTIC CARDIOVASCULAR DISEASE RISK: STUDY AMONG SUBJECTS IN SLEMAN DISTRICT OF YOGYAKARTA INDONESIA - Suhadi, Rita; Virginia, Dita Maria; Setiawan, Christianus Heru (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objectives: The subjects in the Sleman District of Yogyakarta had medium Framingham risk score (FRS) in the preceding year study. The 10-year atherosclerotic cardiovascular disease (ASCVD) risk was a newer risk estimator than FRS. This study aimed to associate the lipid profiles with the ASCVD risk. Methods: The study was conducted with a cross-sectional design and the subjects were selected with cluster random sampling. The association of lipid profiles and ASCVD risk was analyzed with Mannâ€“Whitney/Kruskalâ€“Wallis tests and Spearman's rho correlation, whereas the categorical scores within sub-groups were analyzed Chi-square statistics, respectively. Results: The eligible subjects (n=221) had the age at 51.7Â±8.1 years, systolic/diastolic blood pressure 136.8Â±22.4/85.0Â±12.4 mmHg, total-cholesterol (total-C), high-density lipoprotein-cholesterol (HDL-C), low-density lipoprotein-cholesterol (LDL-C), and triglyceride at 202.0Â±34.9 mg/dl, 52.6Â±12.5 mg/dl, 126.3Â±30.0 mg/dl, and 135.9Â±95.4 mg/dl, respectively; with hypertension treatment 16.7%, smoking 52.9%, diabetes 10.4%, and the median ASCVD risk at 4.4 (0.2-41.4). The ASCVD risk has significant association with non-lipid profiles, total-C, lipid ratio of triglyceride/HDL-C, total-C/HDL-C, and LDL-C/HDL-C, to a lesser extent, HDL-C, LDL-C, and triglyceride. Conclusion: The 10-year ASCVD risk of the subjects was categorized as low and had a significant association with total-C and lipid ratio of triglyceride/ HDL-C, total-C/HDL-C, and LDL-C/HDL-C.